Resilience as a protective factor for secondary school students against tobacco use - José Ramón Martínez-Pérez; Yinet Labrada-Barrera; Lourdes Leonor Bermudez-Cordoví; Yunelsy Ortiz-Cabrera; Elmer Hector Pérez-Leyva (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2024)
Background: resilience is a social skill with great involvement in the prevention and reduction of smoking behavior.